Determinantes sócio-demográficos e clínicos na decisão reprodutiva em mulheres infectadas pelo VIH/SIDA - Pereira, Marco (2008)
Introduction: For a substantial number of women in Portugal, the news of a positive diagnosis of HIV infection occurs during routine prenatal care. These women are confronted with critical decisions in relation to pregnancy. The purpose of this study was to identify and describe medical, demographic and psychological characteristics of HIV-positive women who become pregnant, and also to discriminate the profiles of those who decide to continue pregnancy from those who decide to terminate it, after receiving news of their positive HIV status. Methods: A sample of 36 HIV-infected pregnant women was assessed. Data was collected for the following variables: demographic characteristics (age; race/ethnicity; marital status; socio-economic status), obstetric history, pregnancy information; and HIV-associated information (mode of transmission; knowledge of serological status). Results: Results showed that decision to continue pregnancy was significantly associated with marital status (p<0.01), mode of transmission (p<0.05), knowledge of HIV infection prior to pregnancy (p<0.05) and acceptance of pregnancy (p<0.01). Marital status, mode of transmission and acceptance of pregnancy were the best predictors, explaining a total variance of 61.9% (F=18.302, p <0.001). Discussion: These findings emphasize the importance of HIV testing, not only as a routine procedure during prenatal care, but also in family planning. Childbearing plans should be routinely discussed with non-pregnant infected women, so that they can make their own informed decisions and consider the variety of options currently available.